Study of the mayfly order Ephemeroptera (Insecta) in Brazil: a scienciometric review - Yulie Shimano; Frederico F. Salles; Leandro Juen (Revista Brasileira de Entomologia, 2013)
Study of the mayfly order Ephemeroptera (Insecta) in Brazil: a scienciometric review. Despite an increase in the number of studies in recent years of the aquatic insect order Ephemeroptera (the mayflies) much still remains to be learnt. In order to identify the current state of knowledge of this group in Brazil, we performed a scienciometric analysis with the purpose of identifying the strong and weak points of Brazilian research into the group. Our research used the "Institute for Scientific Information - ISI" database and was based on the abstracts, titles and keywords of manuscripts published between 1992 and 2011. We selected the papers with the combination of the words "Ephemeroptera" and "Brazil*" based on a search in February 2012. We analyzed 92 articles, and noted a lack of studies in some Brazilian states, no specific studies about some families, and an absence of phylogenetic studies. To improve ecological studies, it is necessary to fine-tune taxonomic resolution. Moreover, there is a lack of studies investigating the environmental variables which influence the distribution of mayflies. Despite these gaps, if the rate of publication with mayflies proceeds at the same pace, we anticipate that many of these knowledge gaps will be closed.